Intensive care physicians' perceptions of the diagnosis & management of patients with acute hypoxic respiratory failure associated with COVID-19: A UK based survey. (August 2022) - Dushianthan, Ahilanandan; Cumpstey, Andrew F; Ferrari, Matteo; Thomas, William; Moonesinghe, Ramani S; Summers, Charlotte; Montgomery, Hugh; Grocott, Michael PW
Background: Whilst the management of Coronavirus disease-2019 (COVID-19) has evolved in response to the emerging data, treating such patients remains a challenge, and many treatments lack robust clinical evidence. We conducted a survey to evaluate Intensive Care Unit (ICU) management of COVID-19 patients with acute hypoxic respiratory failure and compared the results with data from a similar survey focusing on Acute Respiratory Distress Syndrome (ARDS) that was conducted in 2013. Methods: The questionnaire was refined from a previous survey of ARDS-related clinical practice using an online electronic survey engine (Survey Monkey®) and all UK intensivists were encouraged to participate. The survey was conducted between 16/05/2020 and 17/06/2020. Results: There were 137 responses from 89 UK centres. Non-invasive ventilation was commonly used in the form of CPAP. The primary ventilation strategy was the ARDSnet protocol, with 63% deviating from its PEEP recommendations. Similar to our previous ARDS survey, most allowed permissive targets for hypoxia (94%), hypercapnia (55%) and pH (94%). The routine use of antibiotics was common, and corticosteroids were frequently used, usually in the context of a clinical trial (45%). Late tracheostomy (>7 days) was preferred (92%). Routine follow-up was offered by 66% with few centres providing routine dedicated rehabilitation programmes following discharge. Compared to the ARDS survey, there is an increased use of neuromuscular agents, APRV ventilation and improved provision of rehabilitation services. Conclusions: Similar to our previous ARDS survey, this survey highlights variations in the management strategies used for patients with acute hypoxic respiratory failure due to COVID-19.